Neurophysiological correlates of tactile width discrimination in humans - Pais-Vieira, Carla; Allahdad, Mehrab K.; Perrotta, André; Peres, André S.; Kunicki, Carolina; Aguiar, Mafalda; Oliveira, Manuel; Pais-Vieira, Miguel (Frontiers in Human Neuroscience, 2023)
Tactile information processing requires the integration of sensory, motor, and cognitive information. Width discrimination has been extensively studied in rodents, but not in humans. Here, we describe Electroencephalography (EEG) signals in humans performing a tactile width discrimination task. Comparison of changes in power between two different periods of the task, corresponding to the discrimination of the tactile stimulus and the motor response, revealed the engagement of an asymmetrical network associated with fronto-temporo-parieto-occipital electrodes and across multiple frequency bands. Analysis of ratios of higher [Ratio1: (0.5-20Hz)/(0.5-45Hz)] or lower frequencies [Ratio2: (0.5-4.5Hz)/(0.5-9Hz)], during the discrimination period revealed that activity recorded from frontal-parietal electrodes was correlated to tactile width discrimination performance between-subjects, independently of task difficulty. Meanwhile, the dynamics in parieto-occipital electrodes were correlated to the changes in performance within-subjects (i.e., between the first and the second blocks) independently of task difficulty. In addition, analysis of information transfer, using Granger causality, further demonstrated that improvements in performance between blocks were characterized by an overall reduction in information transfer to the ipsilateral parietal electrode (P4) and an increase in information transfer to the contralateral parietal electrode (P3). Lastly, analysis of neural correlates of Wide and Narrow stimuli, using a support vector machine, revealed that changes in ratios of higher frequencies also predicted changes in neural encoding of the tactile stimuli in the ipsilateral parietal electrode (P4) within-subjects. These results suggest that tactile width discrimination is characterized by an asymmetrical network of electrodes involving fronto-temporo-parieto-occipital electrodes where overall performance between-subjects is dependent on fronto-parietal electrodes, and improvements in performance within-subjects are dependent on parieto-occipital electrodes.